PERLINDUNGAN HUKUM TERHADAP WANPRESTASI KREDIT PINJAMAN ANGSURAN MODAL KERJA OLEH KOPERASI DALAM PUTUSAN NOMOR 30/PDT.G.S/2018/PN.PWT - Ricky, Ricky; Gunadi, Ariawan (UNES Law Review, 2023)
This study examines the form of legal protection against credit default on working capital installment loans by cooperatives. The type of data used in this research is secondary data, namely data that is not obtained directly from the field or the community, but through literature studies by reviewing and studying books, literature, journals, and internet data. The research approach used is an approach to systematic law, namely research conducted on certain laws and regulations or registered law. The data collection technique used was a literature study, while the data analysis technique was carried out qualitatively. The results obtained from this legal research are a form of legal protection against default on working capital installment loans by cooperatives. So that the Defendant's responsibility is in default for the occurrence of default on working capital installment loan loans by savings and loan cooperatives based on Decision Number 30/PDT.G.S/2018/PN.PWT. Thus the Defendants did not fulfill their abilities, So it can be concluded that the problem is how is the legal protection for the parties in cases of loan default based on court decisions Number 30/PDT.G.S/2018/PN.PWT and namely to make payments for their obligations, so that thus the Plaintiffs had sufficient reasons according to law that the Defendants both individually and jointly had defaulted / broken promises / defaults because they did not pay their obligations to the Plaintiffs.